Development and verification of coarse‐grain CFD‐DEM for nonspherical particles in a gas–solid fluidized bed. Issue 11 (1st September 2022) - Zhou, Lianyong; Ma, Huaqing; Liu, Zihan; Zhao, Yongzhi
Abstract: Computational fluid dynamics coupled with discrete element method (CFD‐DEM) has been widely used to understand the complicated fundamentals inside gas–solid fluidized beds. To realize large‐scale simulations, CFD‐DEM integrated with coarse‐grain model (CG CFD‐DEM) provides a feasible solution, and has led to a recent upsurge of interest. However, when dealing with large‐scale simulations involving irregular‐shaped particles such as biomass particles featuring elongated shapes, current CG models cannot function as normal because they are all developed for spherical particles. To address this issue, a CG CFD‐DEM for nonspherical particles is proposed in this study, and the morphology of particles is characterized by the super‐ellipsoid model. The effectiveness and accuracy of CG CFD‐DEM for nonspherical particles are comprehensively evaluated by comparing the hydrodynamic behaviors with the results predicted by traditional CFD‐DEM in a gas–solid fluidized bed. It is demonstrated that the proposed model can accurately model gas–solid flow containing nonspherical particles, merely the particle dynamics are somewhat lost due to the scaleup of particle size. Finally, the calculation efficiency of CG CFD‐DEM is assessed, and the results show that CG CFD‐DEM can largely reduce computational costs mainly by improving the calculation efficiency of DEM. In general, the proposed CG CFD‐DEM for nonspherical particles strikes a good balance between efficiency and accuracy, and has shown its prospect as a high‐efficiency alternative to traditional CFD‐DEM for engineering applications involving nonspherical particles.